Journalism in Turkey Practices, Challenges, Opportunities - Ince, Devrim; Bezirgan Arar, Yurdagül (Peter Lang International Academic Publishers, 2020)
Journalism in Turkey has an ambivalent characteristic. On the one hand, the social demand for genuine journalism has increased, and on the other hand, news has turned into a tool within the polluted political polarization atmosphere. In the age of fake news and post-truth, practices of journalism in Turkey both contain significantly striking examples of how media professionals overcome the barriers and also give some clues about the changing nature of journalism. The book examines the deep crisis mainstream media experience in Turkey. New-born media institutions, alternatives, their start-up strategies, and transformation of journalism field are scrutinized by qualitative and quantitative methods. The book aims to present a current picture of journalism in Turkey by underlining both historical continuities and breaks from the tradition.